2015
DOI: 10.5424/sjar/2015133-5142
|View full text |Cite
|
Sign up to set email alerts
|

Leaf blade and petiole nutritional evolution and variability throughout the crop season for Vitis vinifera L. cv. Graciano

Abstract: An adequate nutritional state of a crop can be kept by means of a well-designed fertilization plan based on the assessment of the nutrient availability throughout the growing season. The objective of this study was to determine the reliability of leaf blade and petiole diagnosis and the period of validity of their references at both flowering and veraison by means of systematic monitoring throughout the complete growing season. The study was carried out in two plots planted with Vitis vinifera L. cv. Graciano … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 14 publications
(42 reference statements)
3
15
1
Order By: Relevance
“…Diagnostic methods have been assessed in grapevines to determine whether leaf blade or petiole nutrient concentrations better reflect the nutritional status of the vines, and which sampling period results in the most reliable data. Dominguez et al (2015) concluded that leaf blades are preferable to petioles for the diagnosis of N, P, K, Ca, and Mg in 'Graciano' grapevines at both flowering and veraison, owing to lower variability and higher reproducibility, but they showed that Fe, Mn, Zn, Cu, and B in leaf blades and petioles varied differently among vineyards, so it was difficult to determine which was the best tissue for diagnosis. Schreiner and Scagel (2017) showed that N concentrations in 'Pinot noir' grapevine leaf blades at flowering and veraison have a stronger relationship with productivity and must N nutrient concentrations at harvest than petioles, and are less variable and more stable than petiole concentrations.…”
Section: ) Tree Tissue Analysis and Interpretationmentioning
confidence: 99%
“…Diagnostic methods have been assessed in grapevines to determine whether leaf blade or petiole nutrient concentrations better reflect the nutritional status of the vines, and which sampling period results in the most reliable data. Dominguez et al (2015) concluded that leaf blades are preferable to petioles for the diagnosis of N, P, K, Ca, and Mg in 'Graciano' grapevines at both flowering and veraison, owing to lower variability and higher reproducibility, but they showed that Fe, Mn, Zn, Cu, and B in leaf blades and petioles varied differently among vineyards, so it was difficult to determine which was the best tissue for diagnosis. Schreiner and Scagel (2017) showed that N concentrations in 'Pinot noir' grapevine leaf blades at flowering and veraison have a stronger relationship with productivity and must N nutrient concentrations at harvest than petioles, and are less variable and more stable than petiole concentrations.…”
Section: ) Tree Tissue Analysis and Interpretationmentioning
confidence: 99%
“…The higher N concentrations in blades than in petioles were described for several cultivars ( Christensen , ; Romero et al., ). Moreover, Ca, Fe, and Cu concentrations were also greater in blades ( Benito et al, ; Domínguez et al, ). In contrast, petioles showed higher concentrations of K, Mg, Mn, and Zn ( Christensen , ; Schreiner and Scagel , ; Romero et al, ; Domínguez et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Principal component analysis (PCA) was used to determine the vectors that differ from the dependent variables (N, P, K, Ca, Mg, Fe, Mn, Zn, Cu, B), as described by Domínguez et al (). The original variables were standardized to make them to have variance = 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations